Prophetic social sciences: toward an Islamic-based transformative social sciences - ZTF, Pradana Boy (Indonesian Journal of Islam and Muslim Societies, 2011)
This article discusses of one of the most important type of social sciences developedin Indonesian context. In the midst of debate between Western secularsocial sciences and Islamic social sciences, Kuntowijoyo offered a genuine yetcritical formula of social sciences. The formula called Ilmu Sosial Profetik (ISP)attempted to build a bridge between secular social science and Islamic inclinationof social science. This article describes the position of ISP in the context ofcritical position of Muslim social scientists on the hegemony and domination ofOrientalist tendency in studying Islam. At the end, the author offers a conclusionthat ISP can actually be regarded as Islamic-based transformative science thatcan be further developed for a genuine indigenous theory of social sciences fromthe Third World.Artikel ini membahas salah satu tipe paling penting dari ilmu-ilmu sosial yangdikembangkan dalam konteks Indonesia. Di tengah perdebatan antara ilmu-ilmusosial Barat sekuler dan ilmu social Islam, Kuntowijoyo menawarkan formulayang orisinal dan kritis dalam ilmu sosial. Formula yang kemudian disebut denganIlmu Sosial Profetik (ISP) berusaha untuk membangun jembatan antara ilmu sosial sekuler dan kecenderungan untuk melakukan Islamisasi ilmu sosial. Artikelini menjelaskan posisi ISP dalam konteks posisi kritis ilmuwan sosial Muslim padahegemoni dan dominasi kecenderungan orientalis dalam mempelajari Islam. Padaakhirnya, penulis menawarkan kesimpulan bahwa ISP sebenarnya dapat dianggapsebagai ilmu sosial transformatif berbasis Islam yang dapat dikembangkan lebihlanjut sebagai teori sosial yang berkembang dari Dunia Ketiga.